ELECTRONIC EDUCATIONAL RESOURCES AS A FACTOR OF THE SOCIALISATION OF PEOPLE WITH DISABILITIES - Olga Simen-Severskaya (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the description of new forms of e-learning resources. The article reviews the advantages of the using of e-learning resources. The author analyzes the impact of the using of electronic educational resources on the socialization and integration of people with disabilities.